2011
DOI: 10.1177/0022034510391791
|View full text |Cite
|
Sign up to set email alerts
|

Microgenomics of Ameloblastoma

Abstract: A supplemental appendix to this article is published electronically only at http://jdr.sagepub.com/supplemental. ABSTRACT Gene expression profiles of human ameloblastoma microdissected cells were characterized with the purpose of identifying genes and their protein products that could be targeted as diagnostic and prognostic markers as well as for potential therapeutic interventions. Five formalin-fixed, decalcified, paraffin-embedded samples of ameloblastoma were subjected to laser capture microdissection, li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 31 publications
2
44
0
Order By: Relevance
“…DeVilliers et al [10] had earlier suggested that the over-expression of PTCH could be used for chemotherapeutics and from our findings we support this proposition in Nigerian ameloblastoma cases. Shiori et al [17] recently reported that the proliferation of the ameloblastoma AM-1 cell line was significantly inhibited in the presence of SHH neutralizing antibody and cyclopamine.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…DeVilliers et al [10] had earlier suggested that the over-expression of PTCH could be used for chemotherapeutics and from our findings we support this proposition in Nigerian ameloblastoma cases. Shiori et al [17] recently reported that the proliferation of the ameloblastoma AM-1 cell line was significantly inhibited in the presence of SHH neutralizing antibody and cyclopamine.…”
Section: Discussionsupporting
confidence: 87%
“…A study by DeVilliers et al [10] that determined the microgenomic profile of ameloblastoma via several molecular methods reported that most members of the Sonic Hedgehog pathway were under-expressed except for PTCH that was over-expressed by two-folds. They additionally validated protein expression in their study by immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This and the other observed similarity of Wnt‐1 overexpression between UA and KCOT (34) might explain the comparable local invasiveness and recurrence potential in these two neoplasms. Altered Wnt‐10a gene expression in ameloblastoma is putatively mediated by tumor necrosis factor‐α, and this could play an important role in growth and morphological patterning of ameloblastoma (22).…”
Section: Discussionmentioning
confidence: 99%
“…It is composed of an association of hydrochloric acid (12%), EDTA (0.07%), sodium tartrate (0.014%), sodium and potassium tartrate (0.8%) and water (bring to 1,000 mL), that we, arbitrarily, named ETDA, to differentiate it from the classic EDTA. Variations in the relative proportions of the components of this decalcifying solution are found in literature (DeVilliers et al, , Kashireddy and Chakravarthy, ).…”
Section: Introductionmentioning
confidence: 72%